2007
DOI: 10.1016/j.bbi.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Hostility, anger, and depression predict increases in C3 over a 10-year period

Abstract: We examined the relation of hostility, anger and depression to 10-year changes in the third (C3) and fourth (C4) complement in 313, apparently healthy male participants enrolled in the Air Force Health Study (AFHS), a 20-year study designed to evaluate the health consequences of dioxin exposure. Hostility, depression and anger were assessed using subscales from the Minnesota Multiphasic Personality Inventory (MMPI), which was administered in 1985. Given the high intercorrelations among these psychological scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 61 publications
3
28
0
3
Order By: Relevance
“…Following Boyle et al (2007), we examined items from the Cook-Medley Hostility Scale that reflect the cognitive (cynicism and hostile attributions subscales), affective (hostile affect subscale), and behavioral (aggressive responding subscale) components of hostility. Testretest reliability for the AHo was .74 over a 10-year period (Barefoot, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Following Boyle et al (2007), we examined items from the Cook-Medley Hostility Scale that reflect the cognitive (cynicism and hostile attributions subscales), affective (hostile affect subscale), and behavioral (aggressive responding subscale) components of hostility. Testretest reliability for the AHo was .74 over a 10-year period (Barefoot, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Paralleling the findings of Stewart and colleagues [57], Boyle and colleagues [49] showed that a composite score representing the linear combination between depression, hostility, and anger scales predicted ten-year elevations in the third complement protein (C3), which is an additional CAD-related inflammatory marker. Further, the observation by Gimeno and colleagues [53] that the cognitive symptoms of depression were not connected to twelve-year changes in IL-6 and CPR is aligned with the BDI-II subscale analyses of Stewart and colleagues [57], where it was observed that the somatic-vegetative subscale, and not the cognitive-affective one, preceded and predicted subsequent rises in serum IL-6.…”
Section: Depressionmentioning
confidence: 57%
“…However, a reconsideration of its validity and reliability was auspicious [104]. Finally, the findings could be biased due to the low sample size [54] as well as due to the fact that the sample of the trials [49, 52, 54 -57, 59] was restricted to female [56,59], male [49,52,54,55], white [52,57], or hospitalized subjects. Hence, the results of the individual studies cannot be extrapolated to both genders, other ethnic backgrounds, and different settings [54].…”
Section: Limitations/implications For Further Researchmentioning
confidence: 99%
“…1 Interactive effect of depressive symptoms and verbal aggression on changes (from baseline) in systolic blood pressure (measured in mmHg). Predicted values of change in SBP are plotted using coefficients from the final step of the regression analysis at 1 standard deviation above and below the mean for the Buss-Perry verbal aggression scale, and for conventional BDI cut points for high (19) and low (9) levels of depressive symptoms tionship decreased. As noted by Stewart and colleagues [20], this discrepancy could be due to the fact that Miller's participants had significantly greater depressive symptomatology and were more characteristic of a clinically depressed sample.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, Boyle, Jackson, and Suarez [19] found that men characterized as hostile and prone to experience frequent and intense feelings of anger and depression subsequently showed activation of the complement system (i.e., a component of the immune system that helps destroy pathogens) and, specifically, increases in C3 (i.e., a protein implicated in lipid and glucose metabolism), over the course of 10 years. Stewart and colleagues [20] showed that depressive symptoms moderated the influence of hostility on serum interleukin-6 and C-reactive protein among healthy older adults, such that hostility augmented inflammatory processes only in the presence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 97%